Substitution of Re7+ into CaMnO3: an efficient free electron generation dopant for tuning of thermoelectric properties. Issue 45 (14th November 2017) - Shin, J. Felix; Niu, Hongjun; Alaria, Jonathan; Claridge, John B.; Rosseinsky, Matthew J.
Abstract : Highly dense CaMn1− x Re x O3 samples containing heptavalent Re 7+ exhibited ZT of 0.16(3) at 947 K, which is comparable to the highest values reported for dense B-site doped CaMnO3 . Abstract : Highly dense CaMn1− x Re x O3 (0 ≤ x ≤ 0.04) samples were prepared by solid-state synthesis. The effect of Re doping was assessed by the characterisation of crystal structure, oxygen content, and electrical and thermal transport properties. The oxidation state of the substituted Re was determined by X-ray absorption near edge spectra to be Re 7+, and led to expansion of the lattice and an increase in electron carrier concentration due to the formation of Mn 3+ . The thermal behaviour of the electrical conductivity and the thermopower over a wide temperature range allowed identification of different conduction mechanisms: (1) below 110 K, 3D variable range hopping, (2) between 110 and 650 K, small polaron transport, and (3) above 650 K, activation of carriers over a mobility edge. Evaluation of the power factor expected for different dopant oxidation states as a function of dopant concentration shows that the doping strategy using a heavy heptavalent ion allows accessibility of the peak power factor at lower dopant concentrations, lowering the amount of non-ionised impurities, and therefore improves the electronic substitution efficiency, the ratio of activated carriers over the nominal doping concentration, compared to previously studied dopants. An increased power factor and a reduced lattice thermal conductivity are obtained with a peak figure of merit ZT = 0.16(3) at 947 K for CaMn0.98 Re0.02 O3 . This is an approximately two-fold increase compared to undoped CaMnO3, and is comparable to the highest values reported for highly dense B-site doped CaMnO3 .